The Determinants of Supply Chain Responsiveness among Firms in the Manufacturing Industry in Malaysia - Prem Kumar Rajagopal; Nur Atiqah Zahari Azar; Atikah Shamsul Bahrin; Gouri Appasamy; Veera Pandiyan Kaliani Sundram (International Journal of Supply Chain Management, 2016)
The purpose of this study is to verify the significance of supply chain strategies (lean and agile supply chain, strategic supplier partnership and postponement) on achieving supply chain responsiveness. By applying the strategic-choice theory and the resource-based view of ï¬rms to the supply chain, this study has attempted to develop a research model. The model demonstrates the premise that by implementing proper supply chain practices to support and execute supply chain strategy, this will enhance the responsiveness of the supply chain. For that purpose, this study utilizes survey data from 89 senior executives and managers in the purchasing and supply chain functions from manufacturing ï¬rms in Malaysia. By applying multiple regression analysis, this study finds that all supply chain strategies, namely, the lean, agile, strategic supplier partnership and postponement have a positive relationship towards the supply chain responsiveness. For supply chain practitioners, the results indicate that ï¬rms beneï¬t greatly if they consider the strategies of their supply chain and that such a matching would yield to improve the supply chain responsiveness. The paper theoretically develops logic for and empirically shows that all of the supply chain strategies are appropriate practices to enhance supply chain responsiveness. Furthermore, these relationships indicate a contribution to theory that explains how supply chain strategy can result in supply chain responsiveness, through the concurrent deployment of appropriately matched supply chain practices. This research was conducted using a small sample of 89 respondents.